2019
DOI: 10.3171/2019.5.focus18582
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of neurosurgical implant infection rates and associated pathogens: evidence from 1118 postoperative infections

Abstract: OBJECTIVEVarious implanted materials are used in neurosurgery; however, there remains a lack of pooled data on infection rates (IRs) and infective bacteria over past decades. The goal of this study was to investigate implant infections in neurosurgical procedures in a longitudinal retrospective study and to evaluate the IRs of neurosurgically implanted materials and the distribution of pathogenic microorganisms.METHODS Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 93 publications
0
25
1
Order By: Relevance
“…Regardless of indications for performing craniectomy followed by cranioplasty, the infection rates for this neurosurgical procedure compared to the other procedures is higher. In a broad-based study in 2019 by Ying Chen et al, it was revealed that after craniotomies (6.58% Infection rate), cranioplasties had the highest infection rate (5.89%) in neurosurgical procedures [9]. Infections in cranioplasty procedures can occur early or late in the post-operative period.…”
Section: Cranioplasty Flapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of indications for performing craniectomy followed by cranioplasty, the infection rates for this neurosurgical procedure compared to the other procedures is higher. In a broad-based study in 2019 by Ying Chen et al, it was revealed that after craniotomies (6.58% Infection rate), cranioplasties had the highest infection rate (5.89%) in neurosurgical procedures [9]. Infections in cranioplasty procedures can occur early or late in the post-operative period.…”
Section: Cranioplasty Flapsmentioning
confidence: 99%
“…The most common implants used in spine surgery are screws, rods and intervertebral cages. Different materials such as polypropylene-polyester, titanium, and polyetheretherketone (PEEK) are used in spinal surgeries and a study in 2019 revealed that the above-mentioned materials among all other materials used in neurosurgical procedures have the highest rate for infection [9]. Fusion surgeries require the removal of the intervertebral disk and implantation of an intervertebral cage, this in turn can cause spondylodiscitis which in turn can cause colonization and infection of the implanted screws and cages.…”
Section: Screws Rods and Cagesmentioning
confidence: 99%
“…Third, stringent criteria were used to determine each SSI (i.e., SSI definitions of the National Healthcare Safety Network), possibly leading to a lower rate of infection of 0.6% compared with reports of 1.6%-9% in the literature. 23,41,42 Our SSI rate may not account for patients whose admissions for SSI were outside the University of California, San Francisco system. Indeed, these may not have been captured by the data provided to us by the National Healthcare Safety Network.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Approximately one half of craniotomy/craniectomy infections are attributed to S. aureus ( 7 , 16 18 ), a gram-positive pathogen that forms a biofilm on native bone ( 19 ). Infections can be caused by other bacteria and fungi, although these occur at a much lower rate ( 8 , 17 ). Around 30% of the human population is colonized with S. aureus , typically in the nares and skin, and colonized individuals have an increased risk for invasive S. aureus infection ( 20 ).…”
Section: Introductionmentioning
confidence: 99%